2020
DOI: 10.1108/bfj-07-2019-0568
|View full text |Cite
|
Sign up to set email alerts
|

Topic: chemical compositions and mineral content of four selected South African herbal teas and the synergistic response of combined teas

Abstract: PurposeThe present study was carried out to determine (1) essential minerals, total polyphenols, total flavonoids, moisture and ash of four selected South African herbal teas and (2) the effect of blending bush tea with other known commercial herbal teas.Design/methodology/approachThe method used to determine moisture and ash contents followed that of the Association of Official Analytical Chemists (AOAC). Nine minerals were analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…Our findings were not supported by Studzińska-Sroka et al [ 49 ], whose results of TPC in herbal tea blends correlated with a high content of flavonoids in the mixture of mulberry leaves and cinnamon bark (70:30) (2.23 mg QE g −1 herbal blend). The results were also different in research by Malongane et al [ 48 ], where bush tea alone contained the lowest flavonoid content, but the flavonoid content increased in two-component mixtures.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Our findings were not supported by Studzińska-Sroka et al [ 49 ], whose results of TPC in herbal tea blends correlated with a high content of flavonoids in the mixture of mulberry leaves and cinnamon bark (70:30) (2.23 mg QE g −1 herbal blend). The results were also different in research by Malongane et al [ 48 ], where bush tea alone contained the lowest flavonoid content, but the flavonoid content increased in two-component mixtures.…”
Section: Resultscontrasting
confidence: 87%
“…However, the highest TPC was determined in the WTS31 mixture (2.51 g L −1 ). Malongane et al [ 48 ] also reported TPC in two-component herbal teas. They studied the TPC of honeybush ( Cyclopia species ), rooibos ( Aspalathus linearis (Burm.f.)…”
Section: Resultsmentioning
confidence: 99%
“…The IC 50 of honeybush tea (54.98 µg/mL) was higher than that of bush tea (20.82 µg/mL), showing the lowest anti-oxidant activity, while special tea and its blends with bush tea (BS50:50 and BS25:75) showed high anti-oxidant activity, exhibiting IC 50 values of 2.74 µg/mL, 1.33 µg/mL and 0.62 µg/mL, respectively. The higher anti-oxidant activity of special tea may be due to a higher total phenolic and flavonoid content, as indicated in the preliminary study of the current research [ 38 ]. The same study reported that honeybush has the lowest total phenolic content, thus confirming the lower anti-oxidant activity exhibited by honeybush tea in this study.…”
Section: Resultsmentioning
confidence: 97%